A Comprehensive Phylogenetic Analysis of Deadenylases. (January 2013) - Pavlopoulou, Athanasia; Vlachakis, Dimitrios; Balatsos, Nikolaos A.A.; Kossida, Sophia
Deadenylases catalyze the shortening of the poly(A) tail at the messenger ribonucleic acid (mRNA) 3′-end in eukaryotes. Therefore, these enzymes influence mRNA decay, and constitute a major emerging group of promising anti-cancer pharmacological targets. Herein, we conducted full phylogenetic analyses of the deadenylase homologs in all available genomes in an effort to investigate evolutionary relationships between the deadenylase families and to identify invariant residues, which probably play key roles in the function of deadenylation across species. Our study includes both major Asp-Glu-Asp-Asp (DEDD) and exonuclease-endonuclease-phospatase (EEP) deadenylase superfamilies. The phylogenetic analysis has provided us with important information regarding conserved and invariant deadenylase amino acids across species. Knowledge of the phylogenetic properties and evolution of the domain of deadenylases provides the foundation for the targeted drug design in the pharmaceutical industry and modern exonuclease anti-cancer scientific research.